Personality, cognitive appraisal and adjustment in chronic pain patients - Herrero, Ana Mª; Ramírez-maestre, Carmen; González, Vanessa (The Spanish Journal of Psychology, 2008)
This study investigated the relationship between clinical personality patterns and cognitive appraisal as well as their repercussions on adjustment to chronic pain in a sample of 91 patients. It was predicted that clinical personality patterns would be related to adjustment and cognitive appraisal processes, whereas cognitive appraisals would be related to anxiety, depression and levels of perceived pain. The instruments used were as follows: the Millon Clinical Multiaxial Inventory, the Cognitive Appraisal Questionnaire, the Hospital Anxiety and Depression Scale, and the McGill Pain Questionnaire. Multiple regression analyses, the Kruskal-Wallis test, and the Mann Whitney U-test were used to analyse the data obtained. The results show that certain clinical personality patterns were associated with poor adjustment to chronic pain. The use of cognitive appraisal of harm predicted higher anxiety levels and greater perceived pain in chronic pain patients. The use of cognitive appraisals of challenge predicted lower depression levels.